LEARNING METHODS OF DECISION MAKING SKILLS: DISCUSSION, ASSIGNMENT, AND PRACTICE Case Study in Islamic Boarding School of Jagad 'Alimussirry, Indonesia - asmaul lutfauziah (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2020)
Generally, the learning in Islamic boarding schools use classic methods, ie. rote, bandongan, or sorogan. Decision-making skills is one of the skills needed in the 21st century. This study aims to describe the learning method of decision-making skills. This research is a case study in islamic boarding school of Jagad ‘Alimussirry, Indonesia. It is survey research. The data were obtained through a questionnaire that consists of 9 items of the statement by a 4-point Likert scale. The questionnaire were given to 46 students and 5 lecturers after learning. This study also conducted observations during the learning in 5 courses. The observations were made by 2 observers. The results showed that decision-making skills have been taught with good enough category. The learning methods of decision-making skills is discussion, assignment, and practice. The learning concept are: 1) discuss the expectations and the reality to identify problems with good enough category, 2) assign students to gather relevant information by good enough category, 3) discuss the strategies of mapping for all alternative solutions by good less category, and 4) practice to choose the right decision by good enough category. The strategies of mapping the alternative solutions need to be repaired.